2003
DOI: 10.1016/s0896-6273(03)00565-8
|View full text |Cite
|
Sign up to set email alerts
|

Opposing FGF and Retinoid Pathways Control Ventral Neural Pattern, Neuronal Differentiation, and Segmentation during Body Axis Extension

Abstract: Vertebrate body axis extension involves progressive generation and subsequent differentiation of new cells derived from a caudal stem zone; however, molecular mechanisms that preserve caudal progenitors and coordinate differentiation are poorly understood. FGF maintains caudal progenitors and its attenuation is required for neuronal and mesodermal differentiation and to position segment boundaries. Furthermore, somitic mesoderm promotes neuronal differentiation in part by downregulating Fgf8. Here we identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
618
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(668 citation statements)
references
References 90 publications
46
618
4
Order By: Relevance
“…We have noted the same effect of RA in rabbit as well (not shown). RA is a known antagonist of FGF8 signaling (Diez del Corral et al, 2003;Diez del Corral and Storey, 2004;Sirbu and Duester, 2006) and has been reported to act as a negative regulator of GJ conductance (Zhang and McMahon, 2001). These data open the possibility that RA asymmetrically distributed by cilia-driven leftward flow may contribute to the attenuation of GJ permeability and thus counteract the longrange effect of FGF8 on Nodal.…”
Section: Discussionmentioning
confidence: 99%
“…We have noted the same effect of RA in rabbit as well (not shown). RA is a known antagonist of FGF8 signaling (Diez del Corral et al, 2003;Diez del Corral and Storey, 2004;Sirbu and Duester, 2006) and has been reported to act as a negative regulator of GJ conductance (Zhang and McMahon, 2001). These data open the possibility that RA asymmetrically distributed by cilia-driven leftward flow may contribute to the attenuation of GJ permeability and thus counteract the longrange effect of FGF8 on Nodal.…”
Section: Discussionmentioning
confidence: 99%
“…The mathematical formulation concentrates on modeling the role of the FGF signaling gradient, and the resulting developmental anomalies that are observed when the gradient is perturbed. There are emerging models that concentrate on modeling the FGF signaling gradient in more detail (Baker and Maini, 2007;Pourquié [R.E.B., personal communication]): these models consider the negatively regulating interactions of retinoic acid and FGF8, which have been shown to be present along the PSM (Diez del Corral et al, 2002Corral et al, , 2003Diez del Corral and Storey, 2004). Figure 2B illustrates the possible interactions between retinoic acid and FGF8 that lead to gradient formation.…”
Section: Clock and Induction Modelmentioning
confidence: 99%
“…In another study, Tachibana et al established G9a 2/2 embryonic stem cells (ESCs; G9a is a mammalian histone methylase that methylates H3K9) and differentiated them with all-trans retinoic acid (RA), which is known to promote differentiation along a neural lineage (Bohnsack and Hirschi, 2004;Diez del Corral et al, 2003;Pierani et al, 2001;Wong et al, 2008). The G9a 2/2 ESCs were found to have reduced proliferative capabilities and, additionally, it was shown that loss of H3K9 methylation led to an increase of H3K9 acetylation, while conversely, methylation of H3K9 via G9a caused gene silencing and was essential for normal early embryogenesis.…”
Section: Protein Methylation and Ntdsmentioning
confidence: 99%
“…RA is required for normal neuronal differentiation, and the most active site of RA signaling during development is the spinal cord (Diez del Corral et al, 2003). RA pushes cells toward a neural fate, inhibits proliferation, and attenuates Fgf8 expression in the neuroepithelium.…”
Section: Conclusion: Future Directionsmentioning
confidence: 99%